A new intervention in the Nursing Interventions Classification: "Mechanical Ventilation: Noninvasive" - Joaquín Jesús Blanca Gutiérrez; Rafael Muñoz Segura (Fundación para el Desarrollo de la Enfermería, 2008)
With the term of noninvasive mechanical ventilation we refer to any type of ventilatory support that it doesn´t invade the airway to ventilate the patient. The advantage that this contributes is unquestionable, diminishing the rate of infections and other complications associated to the tracheal intubation. In the Nursing Interventions Classification (NIC) we find a very much related intervention, the intervention 3300, with the label of "Mechanical ventilation". If we read the activities included in this intervention, we observe that they are derived cares of the invasive mechanical ventilation, activities includes in the care of intubated patients. With our work, we have produced a new Intervention, its label is "Mechanical Ventilation: Noninvasive", and we have already revised the existent intervention named as "Mechanical Ventilation". Both proposals have been evaluated and accepted for their inclusion in the NIC fifth edition. Methodology: bibliographical revision in CUIDEN PLUS, MEDLINE, CINAHL and LILACS. Results: We present the double proposal, including labels, definitions and activities. Conclusion: the Intervention with code 3300 changes their current label of "Mechanical Ventilation", for the label of "Mechanical Ventilation: Invasive", also changing their definition. A totally new Intervention is included with the label of "Mechanical Ventilation: Noninvasive".